2001
DOI: 10.1590/s0034-70942001000400002
|View full text |Cite
|
Sign up to set email alerts
|

Influência do óxido nitroso na velocidade de indução e de recuperação do halotano e do sevoflurano em pacientes pediátricos

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…The ratio of inspired and expired fraction of sevoflurane tended to be higher in Group 1 ( Figure 3A and 3B). The total induction time was similar to other studies using the same technique of inhalational induction with progressive increases in sevoflurane concentration 9,10 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The ratio of inspired and expired fraction of sevoflurane tended to be higher in Group 1 ( Figure 3A and 3B). The total induction time was similar to other studies using the same technique of inhalational induction with progressive increases in sevoflurane concentration 9,10 .…”
Section: Discussionsupporting
confidence: 85%
“…Tardelli et al 10 found shorter recovery time (153.3 ± 66.4 seconds) using a similar methodology. One possible explanation can be the maintenance of anesthesia with lower concentrations of sevoflurane, as surgical anesthesia was provided by regional block.…”
Section: Discussionmentioning
confidence: 90%
“…These parameters are qualitative and, therefore, depend on the interpretation of the observer, carrying a greater risk of failure of the evaluation. Besides, hemodynamic changes can occur without a direct 23 . The data presented demonstrated that SEF 95% was significantly lower in the nitrous oxide group.…”
Section: Discussionmentioning
confidence: 99%
“…Observouse, ainda neste grupo, maior incidência de agitação psicomotora, como tosse, intensa movimentação e risos. Essa observação foi condizente com os resultados apresentados por Tardelli e col. que não verificaram diferenças nos tempos de indução ou recuperação quando utilizaram a associação óxido nitroso e sevoflurano na anestesia inalatória em pacientes pediátricos 23 . Os dados apresentados demonstram que o SEF 95% apresentou valor significativamente menor no grupo em que se associou óxido nitroso.…”
Section: Métodounclassified